2016
DOI: 10.1681/asn.2015010009
|View full text |Cite
|
Sign up to set email alerts
|

Ly6Chigh Monocytes Protect against Kidney Damage during Sepsis via a CX3CR1-Dependent Adhesion Mechanism

Abstract: Monocytes have a crucial role in both proinflammatory and anti-inflammatory phenomena occurring during sepsis. Monocyte recruitment and activation are orchestrated by the chemokine receptors CX3CR1 and CCR2 and their cognate ligands. However, little is known about the roles of these cells and chemokines during the acute phase of inflammation in sepsis. Using intravital microscopy in a murine model of polymicrobial sepsis, we showed that inflammatory Ly6C high monocytes infiltrated kidneys, exhibited altered mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 57 publications
(55 reference statements)
7
43
1
Order By: Relevance
“…the prior study did not exclude transient AKI of short duration. Our GWAS also failed to confirm findings from a previously published candidate gene study using mouse models (37). This is not unexpected as there is a growing body of literature suggesting that the overlap between murine and human transcriptomes is minimal (38)(39)(40).…”
Section: Original Articlecontrasting
confidence: 61%
“…the prior study did not exclude transient AKI of short duration. Our GWAS also failed to confirm findings from a previously published candidate gene study using mouse models (37). This is not unexpected as there is a growing body of literature suggesting that the overlap between murine and human transcriptomes is minimal (38)(39)(40).…”
Section: Original Articlecontrasting
confidence: 61%
“…In the course of cecal ligature and punctureinduced sepsis, we reported that CX3CR1-dependent Ly6C high -Mo adherence to the renal endothelium exerts a protective effect against kidney injuries. 19 Herein, we extended the role of CX3CR1 in the systemic distribution of Ly6C high -Mo during the early phase of acute inflammation. It is likely that monocyte adherence to the endothelium is an important feature of the compensatory anti-inflammatory response syndrome, 31,32 through interleukin-1 receptor alpha release for instance, 19 and through the cleaning of amyloid b, 33 dead cells, and potential pathogens in the vasculature.…”
Section: Discussionmentioning
confidence: 98%
“…19 Herein, we extended the role of CX3CR1 in the systemic distribution of Ly6C high -Mo during the early phase of acute inflammation. It is likely that monocyte adherence to the endothelium is an important feature of the compensatory anti-inflammatory response syndrome, 31,32 through interleukin-1 receptor alpha release for instance, 19 and through the cleaning of amyloid b, 33 dead cells, and potential pathogens in the vasculature. 25 Margination was still increased at day 7 in CLP-operated mice, suggesting that the regulation between marginated and circulating cells is not only a feature of acute inflammation (data not shown).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The human relevance of potentially protective CX 3 CR1-bearing cells is suggested by the reduced risk of acute kidney injury (AKI) during sepsis of patients expressing the I249 CX 3 CR1 polymorphism, which functionally increases CX 3 CR1-mediated monocyte binding to CX 3 CL1, its cognate ligand. [94] Thus, patrolling monocytes appear to play an important function in maintaining endothelium integrity and thus potentially, immune homeostasis. Of note, CX 3 CR1 is also expressed on CD11c + DCs recruited to the kidney cortex during NTN, an immune-complex mediated disease.…”
Section: Effector and Regulatory Immune Cells And The Renal Inflammatmentioning
confidence: 99%